Short- and Long-Term Effects of Universal Preschool: Evidence from the Arab Population in Israel - Elad DeMalach; Analia Schlosser (Center for Economic Studies and ifo Institute (CESifo), 2024)
We estimate the short- and long-term effects of universal preschool education by analyzing the impact of the Israeli Preschool Law, which mandated the provision of public preschool for ages 3 and 4 starting in September 1999. We focus on the Arab population, who were the main beneficiaries of the first phase of the implementation of the Law, and exploit exogenous variation in universal preschool provision across localities due to the Law's gradual implementation. Our difference-in-differences research design compares cohorts of children in treatment localities before and after the Law's introduction to equivalent cohorts in comparison localities. We find that individuals benefited from the provision of universal preschool along various dimensions: their academic performance in elementary, middle school, and high school improved significantly, and their postsecondary enrollment rates increased substantially. We also find beneficial effects of universal preschool on additional outcomes, such as a reduction in juvenile delinquency among males and a decline in early marriage among females. Results are not driven by changes in maternal income or labor supply. A potential mechanism impacting long-term outcomes was the creation of a better learning environment in elementary and middle school, with a greater sense of security and better relationships with teachers and classmates.
Keywords: I24; I25; J20; 330; early childhood education; preschool